The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1002/chem.201502042
|View full text |Cite
|
Sign up to set email alerts
|

Williamson Ether Synthesis with Phenols at a Tertiary Stereogenic Carbon: Formal Enantioselective Phenoxylation of β‐Keto Esters

Abstract: The enantioselective formation of α-aryloxy-β-keto esters is described for the first time. Lewis acid catalyzed enantioselective chlorination of β-keto esters and subsequent SN 2 reactions with phenols yielded α-aryloxy-β-keto esters with up to 96% ee. Favorskii rearrangement of α-chloro-β-keto esters was also found to give 1,2-diesters with slightly reduced enantiopurity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
29
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(32 citation statements)
references
References 63 publications
0
29
0
Order By: Relevance
“…We recently revealed that the S N 2 reaction of α-chloro-β-ketoesters proceeds smoothly to give the corresponding α-heteroatom-substituted-β-ketoesters with retained enantiopurity, despite the reaction taking place at a tertiary carbon atom2324. Encouraged by this result, we examined the nucleophilic substitution of α-chloroketone 2a (Fig.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…We recently revealed that the S N 2 reaction of α-chloro-β-ketoesters proceeds smoothly to give the corresponding α-heteroatom-substituted-β-ketoesters with retained enantiopurity, despite the reaction taking place at a tertiary carbon atom2324. Encouraged by this result, we examined the nucleophilic substitution of α-chloroketone 2a (Fig.…”
Section: Resultsmentioning
confidence: 93%
“…However, although the desired α-chloroketone 2a was obtained in good yield, the resulting enantioselectivity was poor. We also examined the reaction with a chiral Lewis acid catalyst prepared from a spiro pyridyl monooxazoline ligand L1 and copper(II) trifluoromethanesulfonate because it is known to catalyse electrophilic halogenation of β-ketoesters with high enantioselectivity222324. However, the decarboxylative chlorination of 1a using this catalyst also proceeded with poor enantioselectivity.…”
Section: Resultsmentioning
confidence: 99%
“…The stereoselective synthesis of chiral α-chlorinated carbonyl compounds is an important topic, since these targets can be valuable intermediates for the synthesis of a variety of different biologically active molecules [ 85 86 ]. The main interest in these compounds comes from their versatility for further functionalizations by stereospecific nucleophilic S N 2-type displacement reactions with different nucleophiles [ 66 , 85 87 ]. Accordingly, it comes as no surprise that their asymmetric synthesis has been intensively investigated in the past, either relying on asymmetric (transition)-metal- or organo-catalysis [ 76 , 85 94 ].…”
Section: Reviewmentioning
confidence: 99%
“…Several strategies to access these valuable motives in an enantioenriched fashion have been reported in the past. One option would be to use already α-functionalized (i.e., halogenated) carbonyl compounds and carry out functional group interconversions, like, e.g., stereospecific nucleophilic displacement reactions [ 87 ]. Another powerful strategy would be the use of prochiral α-halocarbonyl compounds for asymmetric Darzens-type reactions to obtain chiral α,β-epoxycarbonyl compounds, which has been rather successfully demonstrated under chiral phase-transfer catalysis in the past [ 18 , 102 104 ].…”
Section: Reviewmentioning
confidence: 99%
“…Several research groups have reported on the asymmetric chlorination of β-keto esters using metal catalysts. [6][7][8][9][10][11][12][13][14][15][16][17] Organocatalysis, meanwhile, has received considerable attention in the area of organic synthesis because, in comparison to reactions involving metal catalysts, it is an environmentally benign method. Synthetic methods for producing α-chlorinated compounds from β-keto esters using organocatalysts have also been developed.…”
mentioning
confidence: 99%